5(х-2)+3x=2-(10-6x)
(7y+14)(0,4y-0,32)=0
5y+1/4+3y+2/16=3
|-3x-6|-9=0

Vlad44kostroma4 Vlad44kostroma4    2   26.03.2020 17:16    1

Ответы
kanyamax kanyamax  12.10.2020 05:35
1)5(х-2)+3х=2-(10-6х)
5х-10+3х=2-10+6х
5х+3х=2+6х
8х=2+6х
8х-6х=2
х=1

2)(7у+14)(0,4у-0,32)=0
(7у+14)*(2/5у-8/25)=0
7у+14=0
2/5у-8/25=0
у=-2
у=4/5=0,8
у1=-2
у2=0,8

3)5у+1/4+3у+2/16=3
8у+3/8=3
8у=3- 3/8
8у=21/8
У=21/64

4)|-3х-6|-9=0
|-3х-6|=9
-3х-6=9
-3х-6=-9
х=-5
х=1
х1=-5
х2=1
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра